2009
DOI: 10.1530/eje-08-0874
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacies of glucocorticoid replacement and improvements by physiological circadian therapy

Abstract: Patients with adrenal insufficiency need lifelong glucocorticoid replacement, but many suffer from poor quality of life, and overall there is increased mortality. Moreover, it appears that use of glucocorticoids at the higher end of the replacement dose range is associated with increased risk for cardiovascular and metabolic bone disease. These data highlight some of the inadequacies of current regimes.The cortisol production rate is estimated to be equivalent to 5.7-7.4 mg/m 2 per day, and a major difficulty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 90 publications
2
76
0
10
Order By: Relevance
“…It is especially important among young people. It predisposes to early osteoporosis, arterial hypertension, diabetes, and hypoandrogenism in women [2,6,7].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
See 3 more Smart Citations
“…It is especially important among young people. It predisposes to early osteoporosis, arterial hypertension, diabetes, and hypoandrogenism in women [2,6,7].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…30% report feeling constant tiredness and severely constrained activity. 48% of patients consider themselves to be handicapped [11,12].…”
Section: Selection Of Patients Qualifying For Non-radical Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 The traditional hydrocortisone replacement dose of 30 mg/day in patients with adrenal insufficiency is likely to result in over-replacement and increased risk for cardiovascular disease and bone loss. For example, it has been shown that bone mineral density (BMD) at the femoral neck and lumbar spine is reduced in patients with Addison's disease, indicating undesirable effects of the replacement therapy.…”
Section: Hydrocortisone Replacementmentioning
confidence: 99%